3‐4: Invited Paper: All‐Inkjet‐Printed Low‐Voltage Organic Thin‐Film Transistors. Issue 1 (28th June 2021) - Jiang, Chen
Abstract : Organic thin‐film transistors (OTFTs) have the advantage of potentially low‐cost manufacturing and mechanical robustness. However, the traditional OTFT requires high operating voltages, thereby constraining its applications in the real world. In this paper, we examine the main issues underlying the OTFT that lead to a high operating voltage. We review printed OTFTs and demonstrate ways to reduce the operating voltage by suppressing the interface trap density. Recent advances in all‐inkjet‐printed low‐voltage organic thin‐film transistors show it is possible for the subthreshold slope to approach the thermionic limit. Based on this technology, an all‐inkjet‐printed ultra‐low‐power high‐gain amplifier, applied to eye movement tracking by detecting human electrooculogram signals, is presented.